Desenvolvimento analítico e farmacotécnico de formas farmacêuticas sólidas de isoflavona de soja - OLIVEIRA, Stela Ramirez de (2010)
Isoflavones are flavonoids found in abundance in grains of soy (Glycine max L.) and its derivatives. These substances have estrogen like structure and weakly estrogenic action. They are used for treatment of menopause symptoms as an alternative to conventional hormone replacement therapies, because they cause fewer side effects. Soy isoflavones are amongst herbal products of great interest to obtain solid dosage forms. High assay variability of isoflavones in commercially available capsules and tablets shows the need of appropriate drug development and quality control for this herbal product. The aim of this work was drug development and quality control of soy isoflavone solid dosage forms, using standardized dry extract of soy. To evaluate the quality of the extract microbiologic and assay analysis of this drug s markers were performed. Results obtained from microbiological test did not show microbiologic contamination of the extract, as Escherichia coli, Staphylococcus aureus, Candida albicans and Aspergillus niger did not grow. To evaluate assay and dissolution percentage of both markers analytical methodology for quantification of daidzein and genistein by high performance liquid chromatography was developed, and also a method to analyze dissolution profile of the obtained tablets. Isocratic method was used for chromatographic analysis of the markers, with mobil phase of methanol with 0.1% of acetic acid, water with 0.1% of acetic acid and acetonitrile in proportion 64:32:4, flow of 0.7 mL/min and temperature of 30°C. At this condition, peaks were symmetric, had resolution lower than 2, with retention times of 3,13 and 3,72 for daidzein and genistein, respectively. Assay evaluation of the markers daidzein and genistein showed that concentrations in the extract were 27,8% and 11,1%, respectively. To accomplish preformulation study, thermal analysis and powder and granules flow evaluation were made. Six formulations of isoflavone tablets were developed, one by direct compression and five by wet granulation. Results of thermal analysis showed no possible extract interactions between tested excipients and extract. Wet granulation was the best method to obatain tablets, because it presented the best compressional properties with flow velocity between 4,5 and 6,7 s/100g and compressibility between 16,85% and 26,06%. GU3 formulation, which presented the best performance according to evaluated parameters, made by wet granulation, showed 92,66% and 92,76% of daidzein and genistein, respectively, disintegration of 15 minutes, and its flow was categorized as excellent. In analytical dissolution method development of isoflavone tablets solubility test was performed to define the best medium, and water with 3% of sodium lauryl sulfate dissolved the greatest amount of daidzein and genistein at tested temperature, 37°C, in comparison with the other medium. Other parameters defined through method development were paddle apparatus, stirring speed of 100 rpm and 900 mL of medium volume. Results showed the possibility to obtain promising solid dosage forms to deliver isoflavone, and optimized quality control methodologies to analyze raw material and finished product.